The Process Models of Design Thinking : A Literature Review and Consideration from the Perspective of Craft, Design and Technology Education - Grönman Satu; Lindfors Eila (Universitetsbiblioteket OsloMet, 2022)
Design thinking (DT) has gained attention over the last few decades in a wide range of contexts beyond the traditional preoccupations of designers. It has changed from the activity of designers to an all-round approach to the innovation process. DT is seen as a human‐centred and systematised approach to problem identification and problem solving. It is a way to create innovation, using the designer’s toolkit to integrate the needs of people, the possibilities of technology and the requirements for business success. DT has also become a pedagogical phenomenon in education due to its relevance in cross-curricular learning and the development of twenty‐first‐century skills.
The aim of this article is to search for common ground between the design thinking process (DTP) and the learning process in craft, design and technology (CDT) education. Learning in CDT education relies on the concept of the holistic craft process (HCP), in which the person, or a group, ideates, designs, implements and evaluates the production process of an artefact. The HCP aims to develop individuals’ ability structure widely by enhancing problem solving, creativity, self-expression and knowledge building. Through a narrative literature review and a qualitative analysis of three well-known DTP models, this article aims to identify the elements and phases of the DTP and determine the possibilities for nurturing the development of HCP as a teaching method for innovation and future skills.